Medicinal plants and traditional treatment practices used in the management of HIV/AIDS clients in Mpigi District, Uganda - (:unkn) unknown (Journal of Herbal Medicine, 2016)
HIV/AIDS is a relatively modern disease that has caused extensive morbidity, mortality and suffering worldwide. Although modern laboratory methods for diagnosis and effective allopathic treatments for HIV/AIDS are available there is limited documentation on practices and treatments used by traditional medicine practitioners (TMPs) in the context of HIV/AIDS. We conducted this study to determine how TMPs of Mpigi and Butambala districts in Uganda diagnose and treat HIV/AIDS and to describe the materials they use. We used an ethnobotanical approach to interview TMPs. TMPs diagnose HIV/AIDS from patients’ own disclosure, history of death of spouse or on the basis of symptoms such as chronic fever. We found that the TMPs administer widely differing herbal medicine formulations with little overlap of plant species to treat HIV/AIDS. The species used are described in this paper. Herbal medicines are prepared in mixtures averaging 20 or more species, and are administered orally and intermittently. Some herbal medicines were reported to have adverse effects and/ or contraindications and the TMPs provided advice concerning their safe use to their patients. Some patients are reported to use herbal medicines concomitantly with ARVs and the clinical consequences of this practice are poorly understood. We conclude that TMPs are experimenting with therapies for HIV/AIDS and that there is need to undertake rigorous efficacy and safety studies as well as controlled clinical studies to validate TMPs’ therapeutic claims.
Keywords: Drug discovery; Traditional treatments; Ethnobotany; Ethnomedicine